Jung and Mr. Punch as Mythologems - Mathers, Dale (Journal of analytical psychology, 2018)
This paper explores how we can make our own mythological version of ‘Jung’ say whatever we want. Excessive veneration gets in the way of his theories being allowed to stand on their own. Understanding ‘Jung’ as a mythologem provides a way out of this intoxication with identification by letting us recollect and re-connect to the Collective Unconscious.